Health Workers’ Attitude Mediates the Relation of Knowledge and Interest in Medical Waste Management Practice - Gita Kartika Dewi; Saryono Saryono; Muslihudin Muslihudin (Publikasi Indonesia, 2024)
Medical waste management is essential to the hospital's operational activities. Health workers are needed to manage medical waste in hospitals because they are in direct contact with it. Therefore, the behaviour of health workers plays a vital role in medical waste management. This study determined the relation of knowledge, awareness, interest, and attitude of health workers on medical waste management practices at Sinar Kasih Purwokerto Hospital, Indonesia. In addition, this study also aims to determine the attitude of health workers in mediating the relation of knowledge, awareness, and interest in medical waste management practices at Sinar Kasih Purwokerto Hospital, Indonesia. The sampling method was cluster random sampling with 68 health workers: general practitioners, dentists, specialists, nurses, sanitisers, and public workers (PW). The data collection tool uses a questionnaire tested for reliability and validity to determine the level of knowledge, awareness, interest, attitude, and practice of medical waste management. Data analysis in this study used Partial Least Square (PLS) testing. This study showed that knowledge and interest had no significant positive effect on medical waste management practices. In contrast, awareness and attitude significantly positively impacted medical waste management practices. In addition, the attitude of health workers mediates the effect of knowledge and interest on medical waste management practices. However, attitude does not mediate the impact of awareness on medical waste management practices. The attitude of health workers is a mediator of knowledge and interest toward medical waste management practices.